Studies on morpho-metric traits in some triploids of Arachis: STUDIES ON MORPHO-METRIC TRAITS IN SOME TRIPLOIDS OF ARACHIS - A MOTHILAL; N MANIVANNAN; L RATHNAKUMAR; A EZHIL (Journal of Oilseeds Research, 2017)
Four triploids viz., Arachis hypogaea L. Cv. VRI 3 x A. diogoi, A. hypogaea L. Cv. VRI 3 x A. benensis, A. hypogaea L. Cv. JL 24 x A. diogoi and A. hypogaea L. Cv. JL 24 x A. benensis were studied along with their respective parents for various vegetative and reproductive traits. Most of the triploids are erect in growth habit with reduced petiole length, stipule length and leaflet size. The triploids produced few flowers with orange standard petals. Pollen fertility percentage ranged from 5.0 to 6.5 in the triploids.